The Effect of Circuit Training On Increasing VO2 Max In Scorpio Jakarta Basketball Players - Syah, Rido Arman; Aulia, Dany; Setiawan, Muhammad Arief; Wijaya, Habibi Hadi; Gemael, Qorry Armen (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The basis for this research is the lack of endurance in Scorpio Jakarta KU-16 basketball players. This research aims to determine the influence of Circuit Training on increasing VO2MAX in Scorpio Jakarta basketball players. This research includes Pre-Experimental research. The population and sample in this study were Scorpio Jakarta basketball players aged 16 years and under, totalling 15 players. The test instrument in this research is the Bleep test. The data obtained were analyzed using the Normality Test ( Shapiro Wilk), Homogeneity Test ( Levene's Statistics ) and Hypothesis Test (T-Test). From the results of this research, the data was processed using the Shapiro-Wilk normality test using the SPSS application. The results of the pretest value show Sig= 0.469>0.05, so the pretest data is declared to be normally distributed and the sig value. at posttest = 0.183>0.05 then the posttest data is declared to be normally distributed. Then the homogeneity test, from the results of the research data, sig = 0.388 > 0.05 was obtained, so the data was declared to have a homogeneous distribution. Next, a hypothesis test was carried out. From the results of the research data from both pretest and posttest data samples, it was found that the Sig. (2-failed ) value was 0.000 < 0.05. It could be concluded that the results of the Hypothesis Test were accepted. So it means that there is an influence of Circuit Training on increasing VO2MAX in Scorpio Jakarta basketball players.